PENDAMPINGAN KAJIAN KITAB NAHWU DI MADRASAH TARBIYYATUL ULAA DEREPAN MENOREH SALAMAN MAGELANG - Yulia Choirun Nisa; Zaenal Abidin (khidmatan, 2024)
Education is a conscious and systematic effort to develop an individual's potential, extending beyond formal schooling. In Derepan Hamlet, Menoreh Village, the Madrasah Diniyyah Tarbiyyatul Ulaa serves as a vital platform for students (santri) from the local area and neighboring hamlets to deepen their religious knowledge (Al-Qur'an, Iqra, Tajwid, etc.). The institution's appeal is supported by effective and distinctive teaching methods. Based on initial observation and assessment, a significant curricular gap was identified: the suboptimal study of Nahwu (Arabic grammar/instrumental science), which is fundamental for comprehending classical Islamic texts (Kitab Kuning). Consequently, the community service team conducted intensive mentoring, contributing to the madrasah's curriculum, specifically through the addition of scheduled studies of Kitab Nahwu (Al-Jurumiyyah) and Ilmu Tauhid (Theology). The goal of this activity was to enhance the quality of the santri's understanding of religious texts and to strengthen the collaborative relationship among the caregivers, ustadzah (teachers), students, and the mentoring team. Program results indicate a significant reinforcement of the students' foundational instrumental knowledge (ilmu alat), which is a crucial prerequisite for pursuing higher studies in advanced Islamic boarding schools (pesantren).